How consumers decide feelings and the hidden mind - Schrank, Jeffrey; Learning Seed Company (Lake Zurich, IL : Learning Seed, 2007)
Shows how advertisers and marketers use their understanding of human's decision making processes to persuade us to buy their products. Discusses the role of logic and emotions in decision-making and examines the part played by the subconscious. Looks at heuristics or'rules of thumb' that consumers use to make decisions easier and evaluates the role of brand names and images in consumer judgments
Title from title screen
DVD Format
With English subtitle
Keywords: Consumer behavior; Decision making; Marketing -- Psychological aspects